Development of Extended Multiple Choice Numeracy Questions Based on the Reeves Model - Amelia, Tasya Faricha; Nawawi, Effendi; Putri, Ratu Ilma Indra; Waty, Evy Ratna Kartika (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
This study aims to develop numeracy questions based on the Reeves development model that produces high-quality numeracy questions. The questions are designed in an expanded multiple-choice format, which allows students not only to choose answers but also to provide in-depth logical reasons. This study uses a design research with a systematic approach involving four main stages in the Reeves model: problem identification and analysis, initial design, prototype development, and implementation and reflection. The research methods include expert validation, small group trials, and field trials involving 26 sixth grade students as research subjects. The results of the study showed that 15 numeracy questions were developed, leaving 10 numeracy questions that were of high quality and had high validity, reliability, varying levels of difficulty, and good discriminatory power. The implementation of the questions showed that the expanded multiple-choice format was able to provide an in-depth evaluation of students' abilities and could help identify weaknesses in students' understanding in more detail. With these results, this study concludes that the Reeves development model is effective for developing high-quality numeracy questions. This research also provides practical contributions for teachers and researchers in designing contextual, valid, and reliable numeracy questions.